A liquid distribution model for a column with structured packing under offshore conditions. (22nd October 2016) - Son, Yongho; Min, Kwangjoon; Lee, Kwang Soon
Abstract: A liquid distribution model for a packed column with structured packing under offshore conditions is proposed. In this paper, permanent tilt and dynamic roll motion were selected as representative offshore conditions for the proposed model, considered to be the most severe offshore conditions. The proposed model is composed of an intersection network model with a liquid split algorithm. Parameter estimation was performed for the proposed model using published experimental data to adjust the parameters in the liquid split algorithm for the considered offshore conditions. A comparison between the liquid distribution of the proposed model and that of literature data was also presented. Using the adjusted parameters and proposed model, the main characteristics of liquid distribution under offshore conditions were investigated. In addition, the effects of column diameter and packed height on liquid distribution were studied. The results obtained from the proposed model could be the basis for the design of an absorption column installed on a buoyant platform like a floating production storage and offloading (FPSO) unit. Highlights: Liquid distribution model under offshore conditions was firstly proposed. The results of proposed model were agreed well with the behaviors of published experimental data. The effects of offshore conditions and column dimensions on liquid distribution were studied.